Women, Peace and Security in ASEAN: Need For Distinct Action Plan - Nair, Tamara (2016)
ASEAN’s move towards a post-2015 community presents an opportune moment to relook at issues surrounding women and their role in this envisioned integration. This is especially so in addressing women’s roles, in a milieu of change and reformation, in bringing about and maintaining peace in the region.